Pengaruh Gaya Kepemimpinan, Lingkungan Kerja, Dan Loyalitas Terhadap Kinerja Pegawai (Studi Kasus Pada Pegawai Kantor Sekretariat DPRD Kota Pasuruan) - Djuariyah Djuariyah; Achmad Agus Priyono; Sulton Sholehuddin (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This study aims to determine and describe the relationship between leadership style, work environment, and loyalty to employee performance. This research method uses quantitative methods. This type of research is explanatory research.The sample in this study were employees of the Pasuruan City DPRD Secretariat Office using purposive sampling with the slovin formula and the results obtained were 41 respondents. Methods of data collection using a questionnaire. The analytical method used in this study is instrument test (validity test and reliability test), normality test, classic assumption test (multicollerity test and heteroscedasticity test), hypothesis test (F test and t test), test the coefficient of determination of data processing using SPSS software 14.0.In the final results of the evaluation of the Government Agency Performance Report (LKJIP) agencies in Pasuruan City will try to improve again in order to achieve even better performance in order to improve the performance of employees in completing tasks in accordance with the allotted time. Especially the Pasuruan City DPRD Secretariat Office will make every effort to create a conducive work environment and provide work facilities needed and used according to their functions.The results of this study indicate that leadership style, work environment, and loyalty simultaneously influence employee performance. Leadership style partially has a significant effect on employee performance, work environment partially has no significant effect on employee performance, and loyalty partially has no significant effect on employee performance. Keywords: Leadership Style, Work Environment, Loyalty, and Employee Performance.